2018
DOI: 10.1038/s41388-017-0045-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor and EGFRvIII in glioblastoma: signaling pathways and targeted therapies

Abstract: Amplification of EGFR and its active mutant EGFRvIII occur frequently in GBM. While EGFR and EGFRvIII play critical roles in pathogenesis, targeted therapy with EGFR-tyrosine kinase inhibitors (TKIs) or antibodies has only shown limited efficacy in patients. Here, we discuss signaling pathways mediated by EGFR/EGFRvIII, current therapeutics, and novel strategies to target EGFR/EGFRvIII-amplified GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
353
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(366 citation statements)
references
References 140 publications
9
353
3
1
Order By: Relevance
“…As a known oncogene of glioma, EGFR overexpression usually occurs as a result of copy number amplification, while in other cases where there is no copy number variation, EGFR has the ability for ligand-independent activation by some point mutations or frame-shifting insertions/deletions. Thus, the activation of EGFR in glioma can be achieved by multiple independent pathways, whether co-exists or not [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…As a known oncogene of glioma, EGFR overexpression usually occurs as a result of copy number amplification, while in other cases where there is no copy number variation, EGFR has the ability for ligand-independent activation by some point mutations or frame-shifting insertions/deletions. Thus, the activation of EGFR in glioma can be achieved by multiple independent pathways, whether co-exists or not [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The epidermal growth factor receptor (EGFR), a glycoprotein with intrinsic tyrosine kinase function, is activated by seven peptide growth factors, such as amphiregulin . The EGFR system has a significant role in several cellular pathological and physiological processes, including motility, differentiation, and proliferation …”
Section: Exosomes and MMmentioning
confidence: 99%
“…106 The EGFR system has a significant role in several cellular pathological and physiological processes, including motility, differentiation, and proliferation. 107 It has been recently observed that this signaling mechanism has a critical role in bone metabolism through influencing both OCs and OBs. 108 Further investigations have found that EGFR ligands can trigger the formation of OCs through decreasing in OBs the expression of OPG.…”
Section: Exosomes and MMmentioning
confidence: 99%
“…The altered EGFR activates the RTK/RAS/PI3K pathway causing excessive proliferation . Experimental therapies, targeting EGFR, such as monoclonal antibodies, EGFRvIII vaccines and small molecular inhibitors, have so far not proven effective . Intratumoral heterogeneity, suboptimal blood barrier penetration, compensatory signaling pathways and secondary mutations are probable causes of resistance toward EGFR targeting drugs .…”
Section: Diffuse Astrocytomas and Oligodendrogliomasmentioning
confidence: 99%